Advanced Educational Technologies for Mathematics and Science
XII, 756 p.
Keywords: This book is the outgrowth of a NATO Advanced Research Workshop, held in Milton Keynes (United Kingdom) in the summer of 1990. The workshop brought together about 30 world leaders in the use of advanced technologies in the teaching of mathematics and science. Many of these participants commented that the workshop was one of the more productive and exciting workshops that they had attended. It was not uncommon to see participants engaged in informal discussion far into the evenings and early mornings, long after formal sessions had ended. It is my hope that this book captures the substance and excitement of many of the ideas that were presented at the workshop. Indeed, the process by which this book has come about has given every opportunity for the best thinking to get reflected here. Participants wrote papers prior to the workshop. After the workshop, participants revised the papers at least once. In a few instances, three versions of papers were written. Some participants could not resist the urge to incorporate descriptions of some of the newer developments in their projects. The papers in this book demonstrate how technology is impacting our view of what should be taught, what can be taught, and how we should go about teaching in the various disciplines. As such, they offer great insight into the central issues of teaching and learning in a wide range of disciplines and across many grade levels (ranging from elementary school through undergraduate college education).